O homicídio qualificado pelo feminicídio: estudos de casos na cidade Manaus - Rubim, Goreth Campos (2017)
Femicide is a new type of qualified homicide, provided by Law 13.104 of March 9, 2015. Its incorporation in art. 211, §2, of the Brazilian Penal Code occurred due to Brazil occupying the 5th position as one of the Countries with the highest rate of death of women as a result of domestic violence, according to the Map of Violence: Women's Homicide 2015, prepared by sociologist and researcher Júlio Jacobo Waiselfisz. The city of Manaus currently occupies the 16th position among the capitals where there are more deaths of women related to domestic and family violence, for this reason it was decided in this research to carry out a case study in nine cases criminal cases of homicides qualified by feminicide in Capital of Amazonas that process in the three stick of the Court of the Popular Jury of this city. The objective of this qualitative research is to understand about this new qualifier, and to identify the profile of the victims and accused, motivations and means of executions of this type of crime in the city of Manaus. That is why bibliographic and analytical research was used to know the history and motivation of the practice of this crime, and especially what are the means to confront this criminal practice. As for the results, it was verified that the homicides qualified by feminicide in the capital of Amazonas are still motivated by exacerbated jealousy and nonconformity after the end of the relationship, possessing a passionate character. In addition the victims studied already had a history of aggressions on the part of its companions, and these besides violent, were users of drugs and alcohol within the family.